Going rogue : rise and shine twenty-nine - Evanovich, Janet (New York : Atria Books, 2022)
Monday mornings aren't supposed to be fun, but they should be predictable. However, on this particular Monday, Stephanie Plum knows that something is amiss when she turns up for work at Vinnie's Bail Bonds to find that longtime office manager Connie Rosolli, who is as reliable as the tides in Atlantic City, hasn't shown up. Stephanie's worst fears are confirmed when she gets a call from Connie's abductor. He says he will only release her in exchange for a mysterious coin that a recently murdered man left as collateral for his bail. Unfortunately, this coin, which should be in the office--just like Connie--is nowhere to be found. The quest to discover the coin, learn its value, and save Connie will require the help of Stephanie's Grandma Mazur, her best pal Lula, her boyfriend Morelli, and hunky security expert Ranger. As they get closer to unraveling the reasons behind Connie's kidnapping, Connie's captor grows more threatening and soon Stephanie has no choice but to throw caution to the wind, follow her instincts, and go rogue. -- adapted from jacket
BPL: David Winn Bishop and Isabel MacPherson Bishop Memorial Fund.
Keywords: Plum, Stephanie -- (Fictitious character) -- Fiction; Plum, Stephanie -- (Fictitious character); Bail bond agents -- New Jersey -- Trenton -- Fiction; Coins -- Fiction; Kidnapping -- Fiction; Ransom -- Fiction; Women bounty hunters -- Fiction; Bail bond agents; Coins; Kidnapping; Ransom; Women bounty hunters; Trenton (N.J.) -- Fiction; New Jersey -- Trenton; Humorous fiction; Detective and mystery fiction; Novels; Detective and mystery fiction; Fiction; Humorous fiction; Novels